The Difference of Occlusal Cant and Favored Chewing Side in Subjects with Complete Dentition: Perbedaan Kemiringan Dataran Oklusal dan Kecenderungan Sisi Pengunyahan pada Subjek dengan Gigi Lengkap - Sofyanti, Ervina; Tambunan, Mirna Rory Yohanita; Boel, Trelia; Siregar, Darmayanti; Aditya Rachmawati (TALENTA, 2020)
The examination of static and dynamic occlusal relationship are important in orthodontic diagnosis. Thus, this study aims to analysis the difference of occlusal cant and favored chewing side. This is cross-sectional study of 70 healthy dental students Universitas Sumatera Utara with complete dentition and have no orthodontics treatment history. The position of tongue spatula across on occlusal of both first bicuspids to assess the existence and degree of the canting occlusal based on extra-oral photograph. The occlusal cant positive if it coincided to inter pupil as transversal references and sectioned with facial midline as a vertical reference more than 3Âº. A modified direct method- visual observation was done to assess the favored chewing side. A chi-square test with p level 0.05 in evaluation of the null hypothesis that states there was a difference of occlusal cant and favored chewing side in those subjects. From 36 subjects with cant occlusal positive, there were 26 subjects with and 10 subjects without favored chewing side. Then, from 34 subjects with cant occlusal negative, there were 14 subjects with and 20 subjects without favored chewing side. There was a significant difference (p=0.017) between occlusal cant and favored chewing side. Subjects with complete teeth showed that favored chewing side tendency of 3,714 more often had an occlusal cant positive compared to favored chewing side negative. In conclusion, the significant difference of occlusal cant and favored chewing side in subjects with complete dentition can be considered as a preliminary study in order to understand the complexity of development of mandibular asymmetry.